Cost-effective bacteria-based bionematicide formula to control the root-knot nematode Meloidogyne spp. on tomato plants - Iis Nur Asyiah; JEKTI PRIHATIN; Ahda Dwi Hastuti; Sugeng Winarso; Lenny Widjayanthi; Dwi Nugroho; Kurniawan Firmansyah; Ankardiansyah Pandu Pradana (Society for Indonesian Biodiversity, 2021)
Abstract. Asyiah IN, Prihatin J, Hastuti AD, Winarso S, Widjayanthi L, Nugroho D, Firmansyah K, Pradana AP. 2021. Cost-effective bacteria-based bionematicide formula to control root-knot nematode Meloidogyne spp. in tomato plants. Biodiversitas 22: 3256-3264. The root-knot nematode, Meloidogyne spp. can infect and cause loss production in various horticultural plants, including tomatoes. In the previous study, we found 3 endophytic bacteria isolates and 1 rhizobacterium isolate that could control several plant-parasitic nematodes. In this study, we formulated these bionematicide isolates with cheap and environmentally friendly organic materials. The formula was fortified using several organic matters, vitamin sources, protein sources, and sugar sources. The research was conducted in an experimental land with a history of severe root-knot nematode infection. The analysis showed that there were 63.7 J2 Meloidogyne spp. per 100 ml of soil on the experimental land. The application was given at a time interval of 2 weeks at the concentration of 0.5%, 1%, 1.5%, and 2%, with a dose of 100 ml per plant. As a negative control, the plant did not give any treatments, and as a positive control, the plant was given 5 g carbofuran per plant. The results revealed that treatment with 2% bionematicide formula concentration showed the best consistent result. This treatment increased canopy wet weight by 38.63% and root dry weight by 106.97% compared to negative control. The P4 treatment was also found effective to increase fruit weight by 33.61% and fruit diameter by 26.16% as compared to negative control. Increased plant growth in P4 treatment was closely related to the total of root-knot suppression and root damage intensity. In the P4 treatment, the total of root-knots and root damage intensities was 44.83% and 32.66%, respectively, compared to the negative control. This suppression also occurred in the nematode population and nematode eggs. In the P4 treatment, the total of Meloidogyne spp. J2 in soil and root was lower by 60.74% and 66.24%, respectively, compared to the negative control. A similar phenomenon also occurred in the total of eggs, which was 79.40% lower than the total of eggs in the negative control. This study provides the latest information about a cost-effective bacteria-based bionematicide formula, which is effective in suppressing Meloidogyne spp. infection in tomato, and promotes the growth and development tomato plant.